The Indirect Path From Mindful Parenting to Emotional Problems in Adolescents: The Role of Maternal Warmth and Adolescents’ Mindfulness - Wang, Yuyin; Liang, Yiying; Fan, Linlin; Lin, Kexiu; Xie, Xiaolin; Pan, Junhao; Zhou, Hui (Frontiers in Psychology, 2018)
Mindfulness has been demonstrated to have positive effects on children’s emotional functioning, and adaptive parenting practices are associated with fewer emotional problems. However, the association between mindful parenting and adolescent emotional problems has not been studied much. In the current study, the indirect path from mindful parenting to adolescent emotional problems was examined, with maternal warmth and adolescent dispositional mindfulness as potential mediators. A sample of 168 mother-child dyads participated in this study. A serial indirect effects model showed mother’s mindful parenting could decrease adolescent emotional problems through adolescent’s perceived maternal warmth and their dispositional mindfulness. Findings of this study imply that intervention in mindful parenting may have benefits for adolescents’ emotional problems through enhancing maternal warmth and children’s trait mindfulness.